Performance Studies of Static Synchronous Compensator and Static Synchronous Series Compensator Modes for Convertible Static Compensator - Abd Halim, Wahidah (2005)
This thesis presents an overview of the emerging Flexible AC Transmission System (FACTS) and Convertible Static Compensator (CSC) technologies. CSC, the flexible multifunctional compensator is an innovation fi-om FACTS technology. These technologies are fully utilized the existing transmission system assets, that improve transmission nationality for economical and environmental reasons. The CSC can occupy as shunt and/or series compensation devices providing various modes. The CSC can operate in 11 different configurations depending on control objectives, for voltage control at bus system as well as power flow control on two existing transmission lines. The CSC can function as a Static Synchronous Compensator (STATCOM), Static Synchronous Series Compensator (SSSC), Unified Power Flow Controller (UPFC) and Interline Power Flow Controller (IPFC). This research work focused on STATCOM and SSSC for CSC as shunt and series controller, respectively. The basic operation of the controllers is explained, together with the circuit configurations and general control strategies. The STATCOM and SSSC are based on a voltage-sourced converter (VSC) which consist of Gate Turn- Off (GTO) Thyristor as the switching devices, are used in this research work to study the performance of the controllers. An 11-bus system as the test system is used throughout the study to verifL the proposed models and its control strategies. The model of the controllers and its control are then validated through PSCAD/EMTDC simulation. Steady-state analysis is done to demonstrate the capability of the controllers designed for improving voltage regulation and power flows in the transmission systems. The result obtained from the simulations clearly showed that the designed STATCOM and SSSC controllers are capable in regulating voltage and increased the transmitting power